The effect of melatonin on in vitro maturation fertilization and early embryo development of mouse oocytes and expression of HMGB1 gene in blastocysts - Majidi, Mohammad (2022)
Antioxidants are commonly used for maturation, fertilization and early development of embryos. Melatonin as an antioxidant have been recently proven to be useful for the assisted reproductive technology. In the present study, we evaluated the roles of melatonin in the in vitro maturation, fertilization, development and also the gene expression of high mobility group box-1 (HMGB1) in the blastocysts. The immature oocytes of BDF1 mice were transferred to the media containing different doses of melatonin (10-6, 10-9, 10-12 M). The blastocysts that developed under in vitro fertilizationfrom each group were stained to determine the cell number of embryos and analyzed to determine the expression level of HMGB1 by real-time PCR. The most effective doses of melatonin for maturation of oocytes were 10-6 and 10-12M (P<0.05). Fertilization rate, early development and the cell number of blastocysts were significantly higher in the group that treated with 10-12 M of melatonin comparing to the other groups. The HMGB1 expression decreased in groups that treated with 10-6M and 10-9M of melatonin and increased in the group that treated with 10-12 M of melatonin, but did not show a significant difference (p˃0.05). From the results, it may be concluded that the melatonin could be effective when the embryos undergo maturation, fertilization and early developmental processes. The HMGB1 expression, as a marker of early development in mice embryos, increased in the groups that treated with low doses of melatonin.